OBSTACLES OF QUR'AN HADITH TEACHERS IN INCREASING THE INTEREST IN LEARNING CLASS X STUDENTS AT MADRASAH ALIYAH AL-ASY'ARIYAH MEDAN KRIO - Kamil, Kamil; Tambunan, Nurhalima (Proceeding International Seminar of Islamic Studies, 2023)
The purpose of this study was to find out what are the obstacles faced by teachers of the Qur'an Hadith in increasing the interest in learning of Class X Students in Madrasah Aliyah Al-Asy'ariyah Medan Krio, Sunggal. This research is qualitative research with informants of Qur'an Hadith teachers, school principals, and four students, namely, grade X IPS3 students and IPA 3 students.      This type of research is qualitative research. In qualitative research, the presentation of data can be done in the form of descriptions or abbreviations, summaries, charts, relationships, categories, flowcharts, or the like. In this case, Miles and Huberman stated that in presenting data is presenting data in qualitative research is in the form of narrative text. The results of this study show that the obstacles faced by teachers of the Qur'an Hadith in increasing the interest in learning of Class X Students in Madrasah Aliyah Al-Asy'ariyah Medan Krio do not have heavy obstacles, only in motivating the learning of Class X Students cannot be done spontaneously but it takes time and process to fix them.